Hydrodynamic and stratigraphic evaluation of marine saline intrusion into the coastal groundwater systems of a major crude oil production region in Southern Nigeria - Mathias M. Nkpoidet; Ndifreke I. Udosen; Jewel E. Thomas (Discover Water)
Abstract Saline intrusion constitutes a significant menace to freshwater resources in coastal aquifer systems, particularly in regions undergoing intensive hydrocarbon exploration and exploitation. This study investigated the spatial distribution of saline intrusion within a major crude oil production region in Southern Nigeria. The investigation was undertaken by integrating geoelectrical methods with hydrogeological analysis to characterize subsurface conditions and aquifer vulnerability. Geo-electrostratigraphic surveys were conducted across the area to delineate subsurface lithology and variations in resistivity. The data acquired were interpreted to derive the Dar-Zarrouk parameters and water quality indicator computations of electrical conductivity (EC) and total dissolved solids (TDS). The investigations revealed the presence of three unique subterranean layers. Maps of longitudinal conductance and transverse resistance highlighted the spatial variability in aquifer protective capacity, susceptibility to salinization, and hydro-potential. The Dar-Zarrouk parameters indicated that the aquifer was highly vulnerable to contamination. Saline incursion was most pronounced at depths less than 30 m, with near-surface strata exhibiting reduced resistivity values indicative of elevated salinity levels. Groundwater EC ranged from 660.3 to 729.5 μS/cm (mean 715.6 μS/cm), while TDS concentrations spanned 422.6–466.9 mg/L (mean 457.9 mg/L). Although the international permissible standards for potable water appeared to be met, the aesthetic quality of water in this region is poor. The elevated saline values have also contributed to accelerated corrosion of metallic infrastructure and degradation of concrete foundations. These findings have broad implications for structural integrity and human health. The findings also offer valuable insights into groundwater flow dynamics and can inform sustainable water resource management strategies in similar coastal environments undergoing anthropogenic pressure. Policymakers should implement robust groundwater monitoring systems, regulate groundwater extraction, and utilize artificial barriers to preclude further groundwater salinization.